2018
DOI: 10.1007/s00259-018-3970-y
|View full text |Cite
|
Sign up to set email alerts
|

Optimal time-point for 68Ga-PSMA-11 PET/CT imaging in assessment of prostate cancer: feasibility of sterile cold-kit tracer preparation?

Abstract: The PSMA-11 sterile cold kit seems to be feasible for use in routine clinical practice, and it has a shorter radionuclide preparation time and is less operator-dependent than the synthesizer-based production method. In addition, early Ga-PSMA-11 PET/CT imaging seems to provide a detection rate comparable with that of standard-delay imaging. Furthermore, the shorter preparation time using theGa-PSMA-11 sterile cold kit and promising value of early PET/CT scanning could allow tailoring of imaging protocols which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
26
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 27 publications
4
26
0
3
Order By: Relevance
“…This performance can be explained by the use of a dual time imaging that facilitates interpretation, especially for node lesions. This has already been described for 68 Ga‐PSMA imaging, with only 1.6% suspicious metastasic target lymph nodes, which showed a marked decrease in tracer uptake on delayed images. Indeed, by pooling 10 different studies, the meta‐analysis showed a predicted positive rate of PSMA ligand PET of 42%, 58%, and 76% for PSA values of 0 to 0.2, 0.2 to 1, and 1 to 2 ng/mL, respectively compared to 58%, 81%, and 82% for our neighboring PSA intervals.…”
Section: Discussionsupporting
confidence: 71%
“…This performance can be explained by the use of a dual time imaging that facilitates interpretation, especially for node lesions. This has already been described for 68 Ga‐PSMA imaging, with only 1.6% suspicious metastasic target lymph nodes, which showed a marked decrease in tracer uptake on delayed images. Indeed, by pooling 10 different studies, the meta‐analysis showed a predicted positive rate of PSMA ligand PET of 42%, 58%, and 76% for PSA values of 0 to 0.2, 0.2 to 1, and 1 to 2 ng/mL, respectively compared to 58%, 81%, and 82% for our neighboring PSA intervals.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, Derlin et al, in a retrospective study, found suitable in vivo uptake characteristics of THP-PSMA (kit-based) and suggested the feasibility of its wider application, with a higher patient throughput (18). Our data support the hypothesis that 68 Ga-PSMA-11 cold kit production may be a promising tool, as previously suggested by Beheshti et al (12) without a detrimental effect on image quality in everyday clinical routine. Kit formulations may allow for a local, on-demand production overcoming the issues posed by the complexity of synthetic procedures, while resulting in higher yields with a standardized, high degree of radiochemical purity.…”
Section: Discussionsupporting
confidence: 87%
“…F-DCFBC,18 F-DCFPyL and PSMA-1007 for their potentially easier production and distribution logistics(9-11). To date,68 Ga-labelled PSMA inhibitor Glu-NH-CO-NH-Lys(Ahx)-HBED-CC ( 68 Ga-PSMA-11) is the most employed radioligand for PET/CT(12). Nowadays, a simplified production and by on September 4, 2020.…”
mentioning
confidence: 99%
“…As described by previous studies, there is a significant increase in SUVmax of PCa lesions on delayed images when evaluating dual time point [ 68 Ga]Ga-PSMA-11 PET/CT imaging [ 18 , 21 , 23 , 24 ]. Beheshti et al reported that this increase relates to suspicious lesions ( p < 0.001) in the prostate bed (11.6 ± 8.2 to 14.8 ± 1.0) as well as to LNs (9.7 ± 5.9 to 12.3 ± 8.8) [ 23 ]. Nevertheless, lesions’ tracer accumulation on early imaging has been sufficient for diagnosis [ 23 ], which is consistent with our results.…”
Section: Discussionmentioning
confidence: 92%
“…Beheshti et al reported that this increase relates to suspicious lesions ( p < 0.001) in the prostate bed (11.6 ± 8.2 to 14.8 ± 1.0) as well as to LNs (9.7 ± 5.9 to 12.3 ± 8.8) [ 23 ]. Nevertheless, lesions’ tracer accumulation on early imaging has been sufficient for diagnosis [ 23 ], which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%